„Młodość czy„Młodość czyli stan serca” – wspomnienie ŚDM w Panamie 2019 i nowe wezwanie dla duszpasterstwa młodychli stan serca” – wspomnienie ŚDM w Panamie 2019 i nowe wezwanie dla duszpasterstwa młodych - Bp Marek Mendyk (Społeczeństwo, 2022)
For many of them, the International Youth Day – as they highlighted – was a beautiful retreat and adventure. It most certainly provided many participants with lots of good spiritual nourishment. However, the fruit developed in their life will depend on the responsibility of each of them. Yet it will also depend on priests who „will always be of young spirit”, shall be their guides, shall support them in discovering their path towards God, as well as teach them how to read and interpret their life experience in light of the Gospel. Only then – thanks to the Holy Spirit – they will be able to see more and farther than the others. And that is where the future of the Church lies. The future depends on those who remain open for the Holy Spirit and not on those who only provide the solutions.